METAL-SULFUR-COH-SILICATE FLUID MEDIATED DIAMOND NUCLEATION IN KOKCHETAV ULTRAHIGH-PRESSURE GNEISS - Hwang S.-L.; Shen P.; Yui T.-F.; Chu H.-T. (My University, 2003)
Submicron metal sulfides, randomly oriented microdiamonds and phlogopite have been identified as multiphase inclusions in garnet of a garnet-clinopyroxene-quartz crustal rock from the Kokchetav Massif in Kazakhstan. Analytical electron microscopy shows that metal sulfides are entrapped among diamond aggregates away from infiltration cracks and do not exhibit any specific crystallographic relationship with associated microdiamonds, thus implying a possible syngenetic nucleation of microdiamonds from a precursive fluid containing dissolved metal sulfides. The diamonds increased in size via a spiral growth mechanism, as manifested by dislocations radiating from nuclei toward faceted surface outcrops.